2010
DOI: 10.1002/adma.201000236
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Bulk Conductivity of Gold Nanowires as Nanoscale Interconnects and the Role of Atomically Smooth Interface

Abstract: The electronics industry has consistently decreased the dimensions of structural components and they are now well into the nanoscale range. Naturally, a significant portion of the chip is composed of interconnects. Besides, the engineering problems associated with short wavelength lithography to achieve smaller components, the performance of increasing number of interconnections has become one of the biggest limiting factors in device performance.[1,2] The power loss, signal degradation, interconnection delays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 53 publications
4
105
0
2
Order By: Relevance
“…Kotov and coworkers have shown that the 92 and 185 nm B diameter Au NWs can possess near-bulk conductivity if the NWs are highly crystalline and are highly smooth. 9 We have reported that the core/shell nanocables of Ag@C are very stable, and the Ag NW core can almost retain the conductivity of bulk silver. 14 The excellent electrical transport properties of Au and Ag NWs make them an ideal candidate as interconnects for linking nanoscale devices, but copper is more abundant and less expensive than gold or silver and is currently widely used in different commercial ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kotov and coworkers have shown that the 92 and 185 nm B diameter Au NWs can possess near-bulk conductivity if the NWs are highly crystalline and are highly smooth. 9 We have reported that the core/shell nanocables of Ag@C are very stable, and the Ag NW core can almost retain the conductivity of bulk silver. 14 The excellent electrical transport properties of Au and Ag NWs make them an ideal candidate as interconnects for linking nanoscale devices, but copper is more abundant and less expensive than gold or silver and is currently widely used in different commercial ways.…”
mentioning
confidence: 99%
“…8,9 Many kinds of one-dimensional (1D) conductive nanomaterials have been intensively exploited in the past few years, such as carbon nanotubes (CNTs), 10 metal NWs (e.g., Ag, 11À16 Au, 8,9 Cu, 17À20 Mo, 21 Pb, 22,23 Pt, 24 etc. ), inorganic compound NWs (e.g., RuO 2 , 25 Ni 3 Si, 26 etc.…”
mentioning
confidence: 99%
“…37. 37 We assumed a surface roughness h ¼ 0.03 nm (atomically smooth), which seems to be justified given the recent results of Critchley et al 37,38 A is the cross-sectional area of the nanowire, and s ext is the extinction cross-section of the nanowires. Fig.…”
mentioning
confidence: 99%
“…3(f) we can also find that the resistivity of the gold nanowire increases obviously with the decrease of its width, which may originate from both the diffuse surface scattering and grain-boundary scattering of the electrons. 27,28 To meet the ever-growing demands for nanoelectronics and nanophotonics, 1,6,7,12,29,30 lots of nanodevices have to be fabricated on insulating substrates such as SiO 2 , quartz glass, and plastics, etc. However, direct-writing-based EBL processes cannot work well with insulating substrates because of the unfavorable and even destructive charging effect.…”
Section: Experimental and Discussionmentioning
confidence: 99%